Depth of Cochlear Implant Array Within the Cochlea and Performance Outcome. (November 2016) - Hilly, Ohad; Smith, Leah; Hwang, Euna; Shipp, David; Symons, Sean; Nedzelski, Julian M.; Chen, Joseph M.; Lin, Vincent Y.W.
Objective: To evaluate whether the depth of cochlear implant array within the cochlea affects performance outcomes 1 year following cochlear implantation. Methods: A retrospective case review of 120 patients who were implanted with the Advanced Bionics HiFocus 1J. Post-implantation plain-radiographs were retrospectively reviewed, and the depth of insertion was measured in degrees from the round window to the electrode tip. Correlation between the depth of insertion and 1-year post-activation Hearing in Noise Test (HINT) scores was analyzed. Intrascala position was not assessed. Results: Depth of electrode insertion ranged from 180° to 720°, and HINT scores ranged from 0% to 100%. A Mann-Whitney U test demonstrated significantly improved 1-year post-activation HINT scores in patients with an insertion depth of 360° or more in comparison with patients with insertion depth of less than 360° (81% vs 61%, P = .048). Patients with 13 to 15 contacts within cochlear turns performed as well as patients with full insertion of all 16 contacts, while patients with only 12 contacts performed poorly. Conclusions: Insertion depth of the AB HiFocus 1J electrode of less than 360° is associated with reduced 1-year post-activation HINT scores when compared with deeper insertions. Partial insertion of 13 active contacts or more led to similar results as full insertion.